Why do extreme events still kill in the São Paulo Macro Metropolis Region? Chronicle of a death foretold in the global south. Issue 1 (2nd January 2021) - Travassos, Luciana; Torres, Pedro Henrique Campello; Di Giulio, Gabriela; Jacobi, Pedro Roberto; Dias De Freitas, Edmilson; Siqueira, Isabela Christina; Ambrizzi, Tércio
ABSTRACT: This paper contributes to the study of climate change and environmental justice with a particular focus on a Global South case-study in the São Paulo Macro Metropolis of Brazil. We also aim to contribute to mandatory critical dialogue between (anticipatory) governance and environmental justice. This study focuses on the rainy seasons from 2016 to 2019. We examine the incidence of 61 extreme precipitation events, as well as 47 deaths caused by rain events, considering their location based on vulnerability indicators. The correlations among these data allow us to reveal the socio-environmental patterns within the relationships between social vulnerability and deaths caused by general rainfall and, more specifically, extreme events. Based on this, we demonstrate that current infrastructure or its lack is one of the reasons why death tolls remain due to the absence of anticipatory governance.